2015
DOI: 10.1002/ajh.23952
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study follow‐up identifies cyclin A2 as a regulator of the transition through cytokinesis during terminal erythropoiesis

Abstract: Genome-wide association studies (GWAS) hold tremendous promise to improve our understanding of human biology. Recent GWAS have revealed over 75 loci associated with erythroid traits, including the 4q27 locus that is associated with red blood cell size (mean corpuscular volume, MCV). The close linkage disequilibrium block at this locus harbors the CCNA2 gene that encodes cyclin A2. CCNA2 mRNA is highly expressed in human and murine erythroid progenitor cells and regulated by the essential erythroid transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Fortunately, advances in both sequencing technology and functional approaches have allowed for the direct study of human erythropoiesis and disorders due to alterations of this process. GWAS coupled with thorough functional follow-up have identified novel roles for BCL11A as an essential HbF silencing factor (Sankaran et al, 2008), CCND3 and CCNA2 as regulators of RBC size and number (Ludwig et al, 2015; Sankaran et al, 2012a), TRIM58 as a regulator of enucleation (Thom et al, 2014), and SMIM1 as a key RBC surface protein encoding the Vel blood antigen (Cvejic et al, 2013). Studies of rare genetic disorders in humans have revealed novel, and sometimes unexpected, findings, such as an erythroid-specific defect due to ribosomal protein haploinsufficiency in Diamond Blackfan anaemia (Ludwig et al, 2014).…”
Section: Model Systems and Organisms Used For Understanding Erythropomentioning
confidence: 99%
“…Fortunately, advances in both sequencing technology and functional approaches have allowed for the direct study of human erythropoiesis and disorders due to alterations of this process. GWAS coupled with thorough functional follow-up have identified novel roles for BCL11A as an essential HbF silencing factor (Sankaran et al, 2008), CCND3 and CCNA2 as regulators of RBC size and number (Ludwig et al, 2015; Sankaran et al, 2012a), TRIM58 as a regulator of enucleation (Thom et al, 2014), and SMIM1 as a key RBC surface protein encoding the Vel blood antigen (Cvejic et al, 2013). Studies of rare genetic disorders in humans have revealed novel, and sometimes unexpected, findings, such as an erythroid-specific defect due to ribosomal protein haploinsufficiency in Diamond Blackfan anaemia (Ludwig et al, 2014).…”
Section: Model Systems and Organisms Used For Understanding Erythropomentioning
confidence: 99%
“…The defects in enucleation in erythroblasts deficient for cyclin A2 were independently confirmed by a recent in vitro study 16 using fetal liver erythroblast culture system. The knockdown of cyclin A2 in fetal liver erythroblasts in culture using short hairpin RNAs led to significant enucleation defects, 16 similar to phenotypes displayed by A2 KO fetal liver erythroblasts and bone marrow in our study. Nevertheless, while they observed proliferation defects, in our study there are only mild or no effects on proliferation.…”
Section: Discussionmentioning
confidence: 66%
“…Our focus has been on using insight from GWAS to identify regulatory elements and the genes they affect to gain new insight into hematopoiesis. For example, we identified variants altering the levels of cyclins D3 and A2, which have key roles in regulating the cell divisions that occur in the last stages of erythropoiesis before the cells prepare to enucleate and form mature RBCs (45,46). It should be noted that over 75 loci have been identified as associated with RBC and other blood cell traits (47), suggesting that there may be more opportunities to gain important new insight into regulators of erythropoiesis and hematopoiesis through more systematic studies.…”
Section: Common Variation In Rbc Traits and Erythropoiesismentioning
confidence: 99%